Herbal Extract Mixture Modulates Intestinal Antioxidative Capacity and Microbiota in Weaning Piglets - Wang, Meiwei; Huang, Huijun; Wang, Lei; Yang, Huansheng; He, Shengwen; Liu, Feng; Tu, Qiang; He, Shanping (Frontiers in Microbiology, 2021)
Recently, the application of herbal extract has developed in multiple aspects, such as medicine, animal feed. Different compositions of herbal extract mixture have various components and diverse functions. This study aimed to evaluate the effects of herbal extract mixture (HEM, Lonicera japonica Thunb, Astragalus membranaceus, Eucommia folium, Codonopsis pilosula) on intestinal antioxidant capacity and colonic microbiota in weaned pigs. A total of 18 piglets [Duroc × (Landrace × Yorkshire)] with the initial body weight of 5.99 ± 0.13kg (weaned at 21days) were randomly divided into two groups (n=9): control group (CON, basal diet) and HEM treatment group (HEM, 1000 mg/kg HEM + basal diet). The experiment period lasted for 14 days. Our results showed that dietary supplementation with HEM modulated the antioxidant capacity through decreasing the activity of superoxide dismutate (SOD) in ileum and glutathione peroxidase (GSH-PX) in serum, decreasing the mRNA expression of Kelch like-ECH-associated protein 1 (Keap1) in the jejunum and the protein level of Keap1 in the ileum. Besides, the composition of colonic microbiota was modified in the HEM group with affected relative abundances of the Firmicutes and Bacteroidetes at the phyla level. Taken together, supplementation of HEM can regulate the antioxidant capacity, and modify the composition of colonic bacteria in weaning piglets. This study provides new insights into the combination function to several of herbal extract in weaning piglets.